2015
DOI: 10.1093/infdis/jiv033
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Influence of Vitamin D in Host Response to SystemicCandidaInfection—Vitamin D Dose Matters

Abstract: Vitamin D level is linked to susceptibility to infections, but its relevance in candidemia is unknown. We aimed to investigate the in vivo sequelae of vitamin D3 supplementation in systemic Candida infection. Implicating the role of vitamin D in Candida infections, we showed that candidemic patients had significantly lower 25-OHD concentrations. Candida-infected mice treated with low-dose 1,25(OH)2D3 had reduced fungal burden and better survival relative to untreated mice. Conversely, higher 1,25(OH)2D3 doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…From the longitudinal data by Lundqvist et al [14] it can be assumed that mothers in the present study who were insufficient post-partum may also have been insufficient during pregnancy. Although the confidence interval of the estimate was wide, resulting in uncertainty, these findings could be consistent with studies reporting vitamin D insufficiency to be associated with susceptibility to a variety of infections as for example respiratory tract infections and candidemia [5] [21] and that vitamin D modulates the immune response to Candida [2]. Cut-off levels for vitamin D were originally set in relation to the role of vitamin D in bone mineralization, with levels <25 nmol/L (10 ng/mL) often referred to vitamin D deficiency and <50 nmol/L (20 ng/mL) as vitamin D insufficiency [11], both associated with decreased bone mineralization and increased fracture risk.…”
Section: Health and Vitamin D Insufficiencysupporting
confidence: 84%
See 1 more Smart Citation
“…From the longitudinal data by Lundqvist et al [14] it can be assumed that mothers in the present study who were insufficient post-partum may also have been insufficient during pregnancy. Although the confidence interval of the estimate was wide, resulting in uncertainty, these findings could be consistent with studies reporting vitamin D insufficiency to be associated with susceptibility to a variety of infections as for example respiratory tract infections and candidemia [5] [21] and that vitamin D modulates the immune response to Candida [2]. Cut-off levels for vitamin D were originally set in relation to the role of vitamin D in bone mineralization, with levels <25 nmol/L (10 ng/mL) often referred to vitamin D deficiency and <50 nmol/L (20 ng/mL) as vitamin D insufficiency [11], both associated with decreased bone mineralization and increased fracture risk.…”
Section: Health and Vitamin D Insufficiencysupporting
confidence: 84%
“…Vitamin D modulates immune function influencing different cell types and it has been shown that vitamin D modify proinflammatory cytokine responses [2] [3] [4]. Further, patients with candidemia had lower levels of vitamin D [5]. Pregnancy and the following postpartum period is a period in life with pronounced vulnerability for vitamin D insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In another experimental study, Candida -infected mice treated with low-dose 1,25(OH) 2 -VD had reduced fungal burden and better survival when compared with untreated mice [ 108 ]. However, those animals treated with higher doses of 1,25(OH) 2 -VD (0.1 and 1 μg/kg) had poorer outcomes [ 108 ].…”
Section: Vitamin D and Fungal Infectionsmentioning
confidence: 99%
“…In another experimental study, Candida -infected mice treated with low-dose 1,25(OH) 2 -VD had reduced fungal burden and better survival when compared with untreated mice [ 108 ]. However, those animals treated with higher doses of 1,25(OH) 2 -VD (0.1 and 1 μg/kg) had poorer outcomes [ 108 ]. The authors concluded that the beneficial immune response of VD supplementation was only achieved with lower doses of 1,25(OH) 2 -VD (i.e., 0.001 and 0.01 μg/kg) [ 108 ].…”
Section: Vitamin D and Fungal Infectionsmentioning
confidence: 99%
“…Animal models and clinical trials have demonstrated the protective effect of vitamin supplementation in several infectious diseases15161718. Indeed, vitamin A or vitamin D supplementation has been proposed as treatment option in diseases such as measles and tuberculosis, respectively1519.…”
mentioning
confidence: 99%